A novel biomarker panel index improves risk stratification after ischemic stroke. (June 2022) - Bicvic, Antonela; Scherrer, Natalie; Schweizer, Juliane; Fluri, Felix; Christ-Crain, Mirjam; De Marchis, Gian Marco; Luft, Andreas R; Katan, Mira
Background: We investigated 92 blood biomarkers implicated in the pathophysiological pathways of ischemic injury, inflammation, hemostasis, and regulation of vascular resistance to predict post-stroke mortality. Aim: Based on the most promising markers, we aimed to create a novel Biomarker Panel Index (BPI) for risk stratification. Methods: In this prospective study, we measured 92 biomarkers in 320 stroke patients. The primary outcome measure was mortality within 90 days. We estimated the association of each biomarker using logistic regression adjusting for multiple testing. The most significant 16 biomarkers were used to create the BPI. We fitted regression models to estimate the association and the discriminatory accuracy of the BPI with mortality and stroke etiology. Results: Adjusted for demographic and vascular covariates, the BPI remained independently associated with mortality (odds ratio (OR) 1.68, 95% confidence interval (CI): 1.29–2.18) and cardioembolic stroke etiology (OR 1.38, 95% CI: 1.10–1.74), and improved the discriminatory accuracy to predict mortality (area under the receiver operating characteristic curve (AUC) 0.93, 95% CI: 0.89–0.96) and cardioembolic stroke etiology (AUC 0.70, 95% CI: 0.64–0.77) as compared to the best clinical prediction models alone (AUC 0.89, 95% CI: 0.84–0.94 and AUC 0.66, 95% CI: 0.60-0.73, respectively). Conclusions: We identified a novel BPI improving risk stratification for mortality after ischemic stroke beyond established demographic and vascular risk factors. Furthermore, the BPI is associated with underlying cardioembolic stroke etiology. These results need external validation.